2017
DOI: 10.1186/s12904-017-0186-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence advance directives completion amongst terminally ill patients at a tertiary hospital in Kenya

Abstract: BackgroundAn advance directive (AD) is a written or verbal document that legally stipulates a person’s health care preference while they are competent to make decisions for themselves and is used to guide decisions on life-sustaining treatment in the event that they become incapacitated. AD can take the form of a living will, a limitation of care document, a do-not-resuscitate order, or an appointment of a surrogate by durable power of attorney. The completion rate of AD varies from region to region, and it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
2
15
0
2
Order By: Relevance
“…However, we propose that these objectives are not mutually exclusive. Studies from multiple LMICs have shown that people desire a good quality of death and there is literature precedent for interest in the concept of ACP from LMICs [11,23,62]. Similarly, participants' responses in our study conveyed a positive association between Good Death and EoL Preparation and Life Completion.…”
Section: 'Being Prepared' For End Of Lifesupporting
confidence: 61%
“…However, we propose that these objectives are not mutually exclusive. Studies from multiple LMICs have shown that people desire a good quality of death and there is literature precedent for interest in the concept of ACP from LMICs [11,23,62]. Similarly, participants' responses in our study conveyed a positive association between Good Death and EoL Preparation and Life Completion.…”
Section: 'Being Prepared' For End Of Lifesupporting
confidence: 61%
“…These themes were developed from JNG’s dissertation chapter on death, dying and bereavement transitions in the context of family caregivers’ experiences of ‘midwifing death’ [ 27 ]; watching and waiting on their terminally ill loved ones as death approached. We utilize the term advance directives in the broader sense of and verbal or written instructions conveying ‘a person’s health care preference while they are competent to make decisions for themselves….’ ([ 28 ], p.1) In our specific context advance directives include wills, do-not-resuscitate (DNR) directives, and other variations of end-of-life conversations and decisions regarding terminally ill cancer patients, and from the perspectives of lay family caregivers. The symbol [] indicates omitted sections of text.…”
Section: Resultsmentioning
confidence: 99%
“…Even so, some of the findings resonate with previously published studies providing a basis for comparative analyses end-of-life matters across varied contexts. For example, a Kenyan based study retrospectively examined advance directives of terminally ill patients based on hospital archived records in a private tertiary hospital [ 28 ]. Findings from this study show that 84.2% of the patients in this study who issued advance directives were cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…While every patient deserves medical care as Article 43(2) of the Kenyan constitution guarantees every person the right to the highest attainable standard of health 10 , not all of them should receive the same type of care, for some the treatment will be for healing purposes and for others it will be palliative care. That is why, regarding the issue of the patients to whom resources should be assigned, at all times human dignity should prevail as a fundamental value of medical care and ethical behavior.…”
Section: Lack Of Informationmentioning
confidence: 99%